The Effect of Temperature and Relative Humidity Inside The Shade Netting on The Growth of Pepper Fruiting Branch Cuttings - Suhermanto Suhermanto; Gusti Rusmayadi; Bambang Fredickus Langai (Postgraduate Program - Lambung Mangkurat University (ULM Press Academic), 2021)
Pepper (Piper nigrum L.) has many benefits, especially in its seeds, commonly used as a food flavoring. Pepper effectively increases appetite, increases the digestive glands' activity, and accelerates fatty substances' digestion. In general, pepper production per unit area in Indonesia is low. The average is below 1 ton of dry pepper per hectare. This low productivity is mainly due to inadequate cultivation techniques, such as improper fertilization and inadequate care. The development of pepper cultivation is still running slowly due to the many obstacles faced by farmers. This productivity could be increased if farmers could apply good and correct cultivation techniques. Generally, pepper cultivation in Indonesia uses standards. This technique is expensive and requires intensive maintenance. The pepper seeds commonly planted by farmers come from running shoots. The experimental design used was the split-plot design with shade netting as the first factor and the administration of husk charcoal as the second factor. Other factors observed were climatic factors, including temperature and relative humidity, bird bud burst time, sprouting time, and root-shoot ratio. The results indicated that the shade netting and husk charcoal treatment on the planting medium significantly affected bird bud burst time, sprouting time, and root-shoot ratio. This study aimed to investigate the effect of climate on the growth of pepper cuttings. The results indicated that the best bird bud burst time occurred in treatment n0 (100%), a0 (1:1) 34.67 days, and not significantly different from n0 (100%) a2 (0: 1) 35.00 days. The best sprouting time occurred in treatment n0 (100%) a2 (0: 1) 32.00 days, not significantly different from n0 (100%) a0 (1: 1) 32.50 days. The root-shoot ratio was significantly different in treatment n0 (100%) a1 (1; 0) 5.28 g.